STRATEGI PEMASARAN JAKARTA SEBAGAI DESTINASI WISATA YANG SELARAS DENGAN PERSEPSI PENDUDUK LOKAL - Budi Budi (Jurnal Ilmiah Hospitality Management, 2016)
Destination image is an important factor in marketing of tourist destinations. Destination image has dimensions of cognitive, affective, and konatif/behavioral. Aligned destination image among locals, tourists, and Destination Marketing Organizations (DMO) is key factor for development of sustainable tourism destinations model. This study aims to investigate Jakarta destination image in local residents’ perception, to test whether cognitive destination image affects affective, cognitive destination image affects the konatif/behavioral, affective destination image affects behavioral. Respondents are people who live in Jakarta for at least the last 2 years, data collection is done through a questionnaire distributed online. Data analysis was performed to validity test, reliability test, significance test, determination test. Results showed that in the view of local residents, Jakarta has a cultural tourism, culinary tourism, recreation sites, and interesting historical sights and fun to visit. Results showed that in the view of local residents, Jakarta has a cultural tourism, culinary tourism, recreation sites, and interesting historical sights, and fun to visit. Cognitive destination image affects affective, cognitive destination image affects conative, affective destination image affects conative..